Accuracy of clinical diagnosis in primary degenerative dementia: correlation with neuropathological findings. - Sulkava, R (1983)
Neuropathological features and causes of death are presented in 27 deceased patients belonging to a prospective series of 71 hospitalised patients with primary degenerative dementia. The clinical criteria for primary degenerative dementia used in the present study were accurate enough to exclude patients with multi-infarct dementia. At necropsy, 82% of the cases had neuropathological changes of Alzheimer's disease. The clinical features of patients with other neuropathological changes are described. The most common immediate cause of death was bronchopneumonia which accounted for 59% of deaths in Alzheimer's disease.